PENGARUH BIAYA PRODUKSI DAN HARGA JUAL TERHADAP PENDAPATAN PETANI KELAPA SAWIT DESA LAMONDAPE KECAMATAN POLINGGONA - Novi Juwita Sari; La Ode Turi; Nichen Nichen (Jurnal Ekonomi Bisnis Kompetif, 2026)
The purpose of this study was to determine the effect of production costs and selling prices on the income of oil palm farmers in Lamundape Village, Polinggona District, Kolaka Regency. This study used a quantitative approach. Data collection was carried out by distributing questionnaires in print form directly to the respondents (oil palm farmers). The population in this study was palm oil farmers in Lamundape Village who farm palm oil. The sample size was determined using random sampling, which amounted to 60 people. The research instruments were tested using validity and reliability tests. This study used multiple linear regression analysis with data processing using the SPSS 26 application. The results of this study indicate that production costs have a positive and significant effect on farmers' income (sig 0.000 < 0.05) with a t-value of 33.142 > t-table 1.671, and that selling prices have a positive and significant effect on farmers' income (sig 0.000 < 0.05) with a t-value of 3.75 > t-table 1.671. simultaneously, production cost and selling prices have a positive and significant effect on the income of oil palm farmers. In addition, the R-squared value of 0.956 shows that production costs and selling prices account for 95.6% of income, while the remaining 4.4% is influenced by other variables.